2017
DOI: 10.1007/s00125-017-4255-x
|View full text |Cite
|
Sign up to set email alerts
|

The case for too little melatonin signalling in increased diabetes risk

Abstract: Genome-wide association studies have detected an association between type 2 diabetes risk and a non-coding SNP located in MTNR1B, the gene encoding melatonin receptor 2 (MT2). Melatonin regulates circadian rhythms and sleep and associates with metabolic disorders. However, the mechanisms underlying these actions are still unclear. Functional genomic, animal and clinical studies have not reached the same conclusions: while some studies have reported that decreased melatonin signalling increases type 2 diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
(23 reference statements)
2
13
0
3
Order By: Relevance
“…22,23 Previous data suggested that decreased melatonin signaling through deleterious MT 2 receptor activity increases type 2 diabetes risk. 24 These results were line with various studies, which showed that high melatonin levels lead to decreased risk of diabetes. 25,26 However, increased melatonin signaling is a risk factor for T2DM.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…22,23 Previous data suggested that decreased melatonin signaling through deleterious MT 2 receptor activity increases type 2 diabetes risk. 24 These results were line with various studies, which showed that high melatonin levels lead to decreased risk of diabetes. 25,26 However, increased melatonin signaling is a risk factor for T2DM.…”
Section: Introductionsupporting
confidence: 89%
“…Results of genome‐wide association studies have shown a relationship between variation of MT 2 ( MTNR1B ) in pancreatic islet cells and type 2 diabetes mellitus (T2DM) occurrence, highlighting the role of MT 2 in T2DM pathogenesis . Previous data suggested that decreased melatonin signaling through deleterious MT 2 receptor activity increases type 2 diabetes risk . These results were line with various studies, which showed that high melatonin levels lead to decreased risk of diabetes .…”
Section: Introductionsupporting
confidence: 75%
“…This melatoninreceptor dysfunction is usually a consequence of melatonin receptors genetic variations (e.g. single nucleotide polymorphisms) and affect either MT1 or MT2 receptors (55,56).…”
Section: Melatonin Physiology Clinical Syndromes and Therapeuticsmentioning
confidence: 99%
“…Many of melatonin's biological effects are mediated by the activation of melatonin receptors . The effects of melatonin are mediated by two receptors, which are expressed in a function‐specific fashion .…”
Section: Discussionmentioning
confidence: 99%
“…Both receptors, but predominantly the MT2 receptor, are subject to internalization, maintaining homeostasis . A previous study suggested that the MT2 receptor regulates β cell function; further, deleterious MT2 receptor activity is known to increase diabetes risk . The stimulatory effects of melatonin on insulin secretion rely that the melatonin receptors couple to G proteins mediating a stimulatory effect on insulin secretion .…”
Section: Introductionmentioning
confidence: 99%